Climate Change and Social Unrest: A 6, 000‐Year Chronicle From the Eastern Mediterranean. Issue 7 (4th April 2020) - Kaniewski, David; Marriner, Nick; Cheddadi, Rachid; Fischer, Peter M.; Otto, Thierry; Luce, Frédéric; Van Campo, Elise
Abstract: The history of the Eastern Mediterranean is punctuated by major crises that have influenced many of the region's established socioeconomic models. Recent studies have underscored the role of drought and temperature oscillations in driving changes but attempts to quantify their magnitude remain equivocal, hindering long‐term assessments of the potential interplay between climate and society. Here, we fill this knowledge gap using a 6, 000‐year pollen‐based reconstruction of temperature and precipitation from Hala Sultan Tekke, Cyprus. We find that major social changes and plague outbreaks often occurred in tandem with cooler climate conditions, with anomalies ranging from −3 ± 0.4 °C to −1 ± 0.5 °C, coupled with changing precipitation patterns. We suggest that major climate changes may weaken societies by affecting primary livelihood systems. This long‐term view highlights recurrent cold periods in the Eastern Mediterranean's climate history and advocates that, despite frequent adversity and pandemics, Near Eastern populations adapted and were ultimately resilient to major climate changes. Plain Language Summary: During the last 6, 000 years, the Eastern Mediterranean's climate has been characterized by several periods of marked climate deterioration and cooling. Many of these cooler phases were punctuated by historical crises and outbreaks of plague, suggesting that climate may partially influence social unrest and the spread of scourges. Drought has always been a significant component of past climate changes, but temperature deviations also appear to be as important in fully comprehending the complex interplay between climate and societies. Key Points: A 6, 000‐year climatic reconstruction from Cyprus suggests that cold conditions have affected past societies as much as drought events Five important cold periods were identified at 5250 ± 20, 4215 ± 40, 3200 ± 90, 1400 ± 70, and 620 ± 20 year BP Each cold period is consistent with a significant instability in precipitation, mainly for winter and spring seasons